DESAIN DAN IMPLEMENTASI UMKM GO DIGITAL BERBASIS WEBSITE UNTUK UMKM KELUARGA KHATULISTIWA PONTIANAK - Dedi Saputra; Muhammad Iqbal; Kartika Handayani (Jurnal Informatika Teknologi dan Sains (Jinteks), 2024)
The use of digital technology in the business world is increasingly becoming an urgent need, especially for Micro, Small and Medium Enterprises ( UMKM ) operating in this modern era. This research aims to design and implement a website-based UMKM Go Digital solution as an effort to overcome the marketing problems faced by Khatulistiwa Family UMKM in Pontianak. The design process involves developing a website platform that allows UMKM to expand their product marketing reach online. The integration of e-commerce features, product information, and contact forms is expected to improve affordability and customer engagement. The implementation of this solution is done by involving UMKM as active partners, so that they can utilize the potential of digital technology to improve operational efficiency and reach new market opportunities. Thus, this research aims to support UMKM to overcome marketing challenges through the implementation of a website-based Go Digital strategy. The results can serve as a reference for other UMKM facing similar problems, as well as supporting digital transformation efforts in supporting the growth and sustainability of UMKM in the information technology era.